Qualitative participatory evaluation of a psychosocial rehabilitation program for individuals with severe mental illness. Issue 2 (3rd April 2017) - Rouse, Jennifer; Mutschler, Christina; McShane, Kelly; Habal-Brosek, Criss
ABSTRACT: Clubhouse International is a nonprofit organization that supports the creation of community-based clubhouses around the world. Using a psychosocial rehabilitation approach, clubhouses provide individuals living with mental illness opportunities to successfully live and work in their communities through a variety of programs including employment opportunities, housing support, case management, and social programs. Progress Place, an accredited clubhouse located in Toronto, Ontario, Canada, partnered with evaluators to better understand their psychosocial rehabilitation approach for individuals with severe mental illness. The purpose of the present study was to undertake a participatory evaluation in order to identify mechanisms of change and recovery outcomes that occur for clubhouse members at Progress Place. In the first phase, six focus groups with staff, members, and board members, were conducted. In the second phase, 11 semistructured group interviews were used to confirm and provide feedback on the mechanisms and outcomes that were found. Analysis of responses revealed specific mechanisms (e.g., elevated sense of respect, autonomy, and purpose) and recovery outcomes (e.g., personhood, feeling at peace, acquiring skills) that occur for clubhouse members. Participants reported that themes accurately represented their experience and felt understood by the evaluators. The present study fills a gap in the psychosocial rehabilitation literature by identifying mechanisms of change that lead to recovery outcomes for members who utilize these programs. This study also provides clear direction for future research examining the breadth of outcomes and change mechanisms.